Unique roles in health promotion of dietary flavonoids through gut microbiota regulation: Current understanding and future perspectives. (15th January 2023) - Li, Zhanming; Ren, Zhongyang; Zhao, Lin; Chen, Lin; Yu, Yue; Wang, Dongxu; Mao, Xuejin; Cao, Guangtian; Zhao, Zhenlei; Yang, Hongshun
Highlights: The interaction of food components affected the digestion of dietary flavonoids. Many factors influenced the health benefits associated with dietary flavonoids. Flavonoids and their metabolites contributed to regulating gut microbiota. Multiple signaling pathways were involved in flavonoid bioactivity modulation. Abstract: Advances in understanding the biological effects of dietary flavonoids and flavonoid-rich foods have been reported. Improving knowledge about their beneficial effects, and mechanisms of action, is crucial for better utilization. However, mechanisms responsible for their health benefits are still unclear. Previous research considered has suggested that gut microbiota might be linked to the metabolism of dietary flavonoids. To understand the bioactivities of dietary flavonoids/flavonoid-rich foods better, and the role of microbiota, we explored systematically 1) types of dietary flavonoids and associated health benefits, 2) low bioaccessibilities and metabolic characteristics, 3) gut microbiota role in regulation, and 4) crosstalk between regulation mechanisms. Current challenges and future perspectives were also considered, offering new research directions and identifying trends in the development of flavonoid-rich food products.